The platysma myocutaneous flap: another option for oral cavity reconstruction - Putra, Primurharsa; Raja Lope Ahmad, Raja Ahmad Al'konee; Mahmud, Ridzo (2007)
Introduction The platysma myocutaneous flap have been described by a variety of learned leaders in head and neck surgery. Its advantages includes: thin, pliable and does not require special surgical skill, equipment, or technique to harvest.